The Effectiveness of Using Canva as Assisted Language Learning Media to Improve Undergraduate Students’ Writing Skill - Imam Fauzi (Universitas Muhammadiyah Tangerang, 2024)
Writing skills are something that all teachers should be aware of. A business pamphlet is one of the writing assignments for economics and business students. This study aimed to determine the differences in the learning outcomes of economics and business students by applying the Canva application as an English learning tool to improve their writing skills. The research design used a quasi-experimental design. The research population is economics and business students for the 2022-2023 academic year. The research sample was taken using a saturated sampling technique with the experimental and control groups. The data analysis technique used is the analysis prerequisite test including the normality test and hypothesis testing. The results showed that the post-test average value of the experimental class students' learning outcomes was 81.94, and the control class was 77.34. The hypothesis testing results showed a significant difference between learning outcomes and student activity in the experimental group, which was better than the control group. Based on the results of the study, it was concluded that the application of the Canva application in learning activities to improve the writing skills of economic and business students which was applied to the experimental class had a significantly greater value than students in the control class using PPT software for learning activities and writing skills. In the learning process, lecturers can develop English learning by using learning applications that are more effective and interesting in improving English learning outcomes and students’ writing skills in accordance with learning objectives.